Rainfall Intensity-Duration-Frequency relationship for Trichy and Kumulur - VANITHA, S.; RAVIKUMAR, V. (Journal of Soil and Water Conservation, 2018)
The rainfall Intensity- Duration- Frequency (IDF) relationship is commonly required for planning and designing of various water resource projects. It is a mathematical relationship between the rainfall intensity, duration and return period. This relationship is determined through statistical analysis of recorded rainfall data. The objective of this study is to derive IDF relationship of rainfall at Trichy and Kumulur. A total durations ranging from 10 minutes to 24 hr (10min, 20 min, 30 min, 60 min,120 min , 180 min, 360 min, 720 min and 1440 min) for return periods of 2, 5, 10, 25, 50 and 100 years were analyzed. In this study, yearly maximum rainfall data for Trichy (1951-2010) and Kumulur (1991-2014) were used. Empirical reduction formula of India Meteorological Department (IMD) has been used to estimate the short duration rainfall intensity from yearly maximum rainfall data. Gumbel and Log Pearson Type III (LPT III) Distribution method was used to develop IDF curves and equations. The results obtained using Gumbel method is somewhat higher than the outcomes obtained using the LPT III distribution method. The chi-square goodness of fit test was used to determine the best fit probability distribution. The parameters of the IDF equations and coefficient of correlation for different return periods (2, 5, 10, 25, 50 and 100 years) were calculated by using least square method. The results obtained revealed that in all the cases the correlation coefficient is very high representing the goodness of fit of the formulae to estimate IDF in the station of interest.